Control over Reactive Power of Electric Power Stations for Higher Stability of Electric Power Systems - E. V. Kalentionok; I. D. Filipchik (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The proposed new method for distribution of reactive load between generators of electric power stations serves to ensure higher stability. The paper has determined on the basis of calculations pertaining to steady-state and transitional conditions that application of the given method leads to significant higher safety factor of static stability for active power and increases   limit clearing time of a short circuit.